N, S doped carbon dots—Plasmonic Au nanocomposites for visible-light photocatalytic reduction of nitroaromatics. Issue 23 (26th September 2018) - Mahto, Madhusudan Kr.; Samanta, Dipanjan; Konar, Suraj; Kalita, Himani; Pathak, Amita
Abstract: Abstract : Herein, we report N, S co-doped carbon dots (NS CDs) as stabilizing and reducing agents for the synthesis of N, S doped carbon dots-Au nanocomposites (NS CDs-Au NCs) through the solution method and explore the catalytic property of the synthesized nanocomposites in the reduction of nitro aromatic compounds (NACs) such as 4-nitrophenol (4-NP), 4-nitroaniline (4-NA), and nitrobenzene (NB). The appraisal of the catalytic efficacy of the NS CDs-Au NCs was premised on real time monitoring of the reduction of NACs using UV-Visible absorption spectroscopy. The apparent rate constants (kapp ) of reduction were found to follow the pseudo-first-order kinetics having values of 1.37 × 10 −1, 8.9 × 10 −2, and 5.35 × 10 −2 s −1 for 4-NP, 4-NA, and NB, respectively. The apparent rate constant (1.37 × 10 −1 s −1 ) observed for the reduction of 4-NP by NaBH4 using NS CDs-Au NCs has been found to be one of the highest values reported in the literature so far thereby validating their excellent efficacy as a catalyst.